THE EFFECTS OF BORROWER CHARACTERISTICS ON LOAN DEFAULT FROM BANK KERJASAMA RAKYAT LOAN OFFICER’S PERSPECTIVES - Siti Nur Amira Binti Othman; Zatul Karamah Binti Ahmad Baharul Ulum; Ku Nur Ilyani Binti Ku Abd Aziz; Nabihah Binti Aminaddin4 (International Journal of Accounting, Finance and Business, 2024)
Micro-enterprise sectors are essential to national and economic growth. To support the viability of micro-businesses, the government has established alternatives to aid the Bank Kerjasama Rakyat Berhad in the microfinancing program. Despite the available alternatives, microbusinesses face criticism for the issue of loan defaults. Loan defaults continue to happen even though DFI loan officers can categorize their customers into distinct classes using credit scoring tools. The purpose of this study is to ascertain, from the viewpoints of loan officers the relationship between borrower characteristics and loan default. The underpinning theory is Behavioural Finance Theory. Purposive sampling was used in a quantitative way to choose the sample size. Data were obtained from 129 loan officers in Bank Kerjasama Rakyat through a questionnaire survey. The Partial-Least Square (PLS-SEM) technique of data analysis was employed to test the hypothesized relationship and findings show that borrower characteristics has a significant relationship with loan default.